A new approach to assessing the crossflow membrane filtration of beer at laboratory scale. Issue 4 (2nd October 2018) - Kupetz, M.; Rott, M.; Kleinlein, K.; Gastl, M.; Becker, T.
Abstract : The filterability of beer is influenced by filtration technology as well as beer composition. Because of this, it is difficult to predict the filterability of beer at a laboratory scale. Over the years, various approaches for the measurement of filterability have been proposed, which are neither informative nor practical for the assessment of crossflow membrane filtration. Therefore, the aim of this study was the development of a test to determine filter efficiency and performance of beer during crossflow membrane filtration (CFMF). In this context, filter efficiency describes the ratio of filtered beer volume between two filter periods, which are interrupted by an intermediate cleaning step of the polyether sulfone membranes. The comparison of 32 beer samples and their filter efficiency had an average difference of 1.8% between industrial and laboratory scale. Furthermore, evaluation of filter performance was performed on the basis of industrial CFMF data. Three categories of filter performance at industrial scale were defined – 'bad' (0–1.5 hL/m 2 ), 'acceptable' (1.5–3 hL/m 2 ) and 'good' (>3 hL/m 2 ) – and compared with a corresponding flow rate resulting in a correlation of r  = 0.867 ( p  < 0.001). Therefore, the developed membrane filter test allows the prediction of filter efficiency and performance for CFMF based on one method. Owing to the good comparability of the results, the filter test can be used for the prediction of filterability, together with the optimisation of filtration and membrane cleaning processes as well as daily production scheduling. © 2018 The Institute of Brewing & Distilling